In the Lake of the Woods - O'Brien, Tim, 1946- (New York, N.Y. : Penguin Books, 1995)
The author of The Things They Carried offers a riveting novel of love and mystery. When long-hidden secrets about the atrocities he committed in Vietnam come to light, a candidate for the U.S. Senate retreats with his wife to a lakeside cabin in northern Minnesota. Within days of their arrival, his wife mysteriously vanishes into the watery wilderness.
Originally published: Boston : Houghton Mifflin/Seymour Lawrence, 1994.
Includes bibliographical references.
Keywords: Married people -- Minnesota -- Fiction; Missing persons -- Minnesota -- Fiction; Politicians -- Minnesota -- Fiction; Minnesota -- Fiction; Domestic fiction